A high step-up DC–DC converter based on ASL and VMC for renewable energy applications. (November 2022) - Marzang, Vafa; Babaei, Ebrahim; Mehrjerdi, Hasan; Iqbal, Atif; Islam, Shirazul
Abstract: In this paper, a new high step-up non-isolated DC–DC converter has been proposed and analyzed. The proposed topology provides a high DC output voltage, which is adjustable by two different duty cycles. Moreover, low voltage stress across the power switches can be marked as another advantage of this structure. The inequality of the switches' duty cycles helps obtain high output voltage with moderate duty cycles in this converter. Four inductors based on two magnetic cores, four capacitors, two diodes, and three switches make up the converter's components. Operational modes of the proposed topology are investigated under steady-state analysis in continuous conduction mode (CCM), discontinuous conduction mode (DCM), and boundary condition mode (BCM). In addition, mathematical calculations of voltage, current, and efficiency are provided in this paper. In addition, a comparison study of the proposed converter and other related structures is conducted to determine the advantages it offers. The proportion of losses and efficiency calculation are analyzed. Finally, a (500 W, 50 kHz) laboratory prototype is assembled and analyzed to validate the analytical findings in this paper.